Feasibility of polyetherketone (PEK) composites: a solution for long-term nuclear waste storage. (2016) - Ajeesh, G.; Bhowmik, Shantanu; Sivakumar, Venugopal; Varshney, Lalit; Kumar, Virendra; Abraham, Mathew
This investigation highlights the effect of radiation, chemical and thermal environments on mechanical and thermal properties of polyetherketone (PEK) composites and its rationale for long-term nuclear waste storage. The tests are conducted on samples manufactured using PEK and PEK reinforced with modified carbon nano fibre (CNF). The specimens are subjected to gamma radiation doses of 5 MGy, which is equivalent to the cumulative dosage of radiation from spent nuclear fuel until the radioactivity neutralises completely. Studies under transmission electron microscopy (TEM) reveal that there is a uniform dispersion of modified CNF in PEK. Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) indicate that there are no significant changes in thermal properties of PEK and PEK composite when exposed to aggressive environments. It is observed that tensile strength of polymeric samples remains unchanged when exposed to gamma radiation and thermo-chemical environment.